Defining Benchmarks for Adenoma Detection Rate and Adenomas Per Colonoscopy in Patients Undergoing Colonoscopy Due to a Positive Fecal Immunochemical Test. (December 2016) - Hilsden, Robert J; Bridges, Ronald; Dube, Catherine; McGregor, Elizabeth S; Naugler, Christopher; Rose, Sarah M; Rostom, Alaa; Heitman, Steven J
Abstract : Objectives: Although there is an accepted benchmark for adenoma detection rate (ADR) in average risk screening colonoscopy, a benchmark for ADR or the associated quality indicator, adenomas per colonoscopy (APC), for colonoscopies performed for a positive fecal immunochemical test (FIT+) has not been established. The purpose of this study was to propose methods for establishing a benchmark ADR and APC for FIT+ patients. Methods: In this historical cohort study, we included 15, 329 patients aged 50–74 years who underwent a colonoscopy at Alberta Health Services' Colon Cancer Screening Centre, Calgary, Canada, from 1 January 2014 to 30 June 2015 for either investigation of a positive FIT or average risk screening. Using meta‐regression, we estimated for FIT+ patients the ADR and APC that corresponded to (Method #1: minimally acceptable) an ADR of 25% in average risk individuals, (Method #2: standard of care) the average ADR or APC in all FIT+ patients, and (Method #3: aspirational) the average FIT+ ADR or APC in colonoscopies performed by endoscopists with an ADR of ≥35% in average risk patients. Results: At least one adenoma was detected in 30% of average risk patients and 58% of FIT+ patients. The calculated benchmark FIT+ ADRs for the three methods were 55, 60, and 65%, respectively. The calculated benchmarks for FIT+ APC were 1.2, 1.4, and 1.7, respectively. To account for expected random variation in individual endoscopists' ADR or APC, we propose using the upper bound of the 95% confidence interval of an endoscopist's ADR or APC to determine if they fall below a given benchmark. Conclusions: We have proposed methods of defining benchmarks for ADR and APC in FIT+ patients that go beyond the current "minimally acceptable" threshold currently recommended in average risk patients. These new thresholds represent results obtained by all peers and by a group of expert adenoma detectors defined in an independent patient cohort (average risk). Because the true adenoma burden in FIT+ patients could vary based on factors such as the threshold used to define a positive FIT, screening programs or endoscopy units may need to calculate their own benchmarks using local data.